High-Power-Density, High-Energy-Density Fluorinated Graphene for Primary Lithium Batteries - Zhong, Guiming; Chen, Huixin; Huang, Xingkang; Yue, Hongjun; Lu, Canzhong (Frontiers in Chemistry, 2018)
Li/CFx is one of the highest-energy-density primary batteries; however, poor rate capability hinders its practical applications in high-power devices. Here we report a preparation of fluorinated graphene (GFx) with superior performance through a direct gas fluorination. We find that the so-called “semi-ionic” C-F bond content in all C-F bonds presents a more critical impact on rate performance of the GFx in comparison with sp2 C content in the GFx, morphology, structure, and specific surface area of the materials. The rate capability remains excellent before the semi-ionic C-F bond proportion in the GFx decreases. Thus, by optimizing semi-ionic C-F content in our GFx, we obtain the optimal x of 0.8, with which the GF0.8 exhibits a very high energy density of 1073 Wh kg-1 and an excellent power density of 21460 W kg-1 at a high current density of 10 A g-1. More importantly, our approach opens a new avenue to obtain fluorinated carbon with high energy densities without compromising high power densities.